Comparison of international societal guidelines for the diagnosis of suspected pulmonary embolism during pregnancy. Issue 3 (March 2020) - Cohen, Stuart L; Feizullayeva, Chinara; McCandlish, John A; Sanelli, Pina C; McGinn, Thomas; Brenner, Benjamin; Spyropoulos, Alex C
Summary: Pregnancy-associated pulmonary embolism is one of the leading causes of maternal mortality. Diagnosis of pulmonary embolism in pregnancy is challenging, with symptoms of pulmonary embolism mimicking those of pregnancy. Several key components such as clinical prediction tools, risk stratification, laboratory tests, and imaging widely used for diagnosis of pulmonary embolism in the non-pregnant population show limitations for diagnosis in pregnancy. Further, because of the difficulty of studying pregnant patients, high-quality research evaluating the performance of these diagnostic components in pregnancy is scarce. Seven international medical society guidelines present clinical diagnostic pathways for evaluation of pulmonary embolism in pregnancy that show conflicting recommendations on the use of these diagnostic components. This Review assesses all key components of diagnostic clinical pathways recommended by guidelines for evaluation of pulmonary embolism in pregnancy, reviews current evidence, compares the guideline recommendations with respect to each key component, and provides our preferred diagnostic pathway. It provides the guidelines and available data needed for informed decision making to diagnose pulmonary embolism in pregnancy.